Redescription of the larva of Neoerythromma cultellatum (Hagen in Selys, 1876) (Odonata: Coenagrionidae: Coenagrioninae) - Román-Heracleo, Jareth; Springer, Monika; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2020)
The final instar of Neoerythromma cultellatum (Hagen in Selys, 1876) is redescribed and illustrated based upon reared specimens from Turrialba, Cartago, Costa Rica. This is a detailed complement of the original description provided by García-Díaz (1938) and illustrated with high quality photos of the larval morphology. The larva of N. cultellatum is characterized by a slender, spinulose, and yellow to yellowish-brown body, premental setae 3+1, five palpal setae, male cerci long, and caudal lamella lanceolate, with obvious node, spotted, and markedly tracheate.